Intensification of livestock feed production in Ethiopian highlands: Potential and experiences of the African Highlands Initiative - Amede, Tilahun; Mengistu, S; Roothaert, R. (EVA, 2005)
Livestock production is an essential part of subsistence systems in the Ethiopian highlands. In this paper we are reviewing the role of existing feed resources, and the potential for improving feed systems and intensification pathways in an integrated way.